2021
DOI: 10.1002/ece3.7373
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial ecology of the Critically Endangered Fijian crested iguana (Brachylophus vitiensis): Effects of captivity status and host reintroduction on endogenous microbiomes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Currently, the gut microbiota has been widely studied in invertebrates (Clark and Walker, 2018), amphibians (Bletz et al, 2016) and reptiles (Trevelline et al, 2019;Zhang et al, 2019Eliades et al, 2021, mammals (Hu et al, 2017;Song et al, 2017;Li et al, 2021), and birds (Ryu et al, 2012;Waite et al, 2012;Grond et al, 2018). In recent years, research into the gut microbiota in captive animals, such as Takydromus septentrionalis (Zhou et al, 2020), Neotoma albigula (Martínez-Mota et al, 2020), and Macaca mulatta (Chen et al, 2019) has also attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, the gut microbiota has been widely studied in invertebrates (Clark and Walker, 2018), amphibians (Bletz et al, 2016) and reptiles (Trevelline et al, 2019;Zhang et al, 2019Eliades et al, 2021, mammals (Hu et al, 2017;Song et al, 2017;Li et al, 2021), and birds (Ryu et al, 2012;Waite et al, 2012;Grond et al, 2018). In recent years, research into the gut microbiota in captive animals, such as Takydromus septentrionalis (Zhou et al, 2020), Neotoma albigula (Martínez-Mota et al, 2020), and Macaca mulatta (Chen et al, 2019) has also attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research into the gut microbiota in captive animals, such as Takydromus septentrionalis (Zhou et al, 2020), Neotoma albigula (Martínez-Mota et al, 2020), and Macaca mulatta (Chen et al, 2019) has also attracted extensive attention. The gut microbiota of captive animals may differ from those of wild animals due to dietary differences, antibiotic treatment, human activities, and exposure to other species in captivity (Alfano et al, 2015;Clayton et al, 2016;Chen et al, 2019;Eliades et al, 2021). Studies on mammals and reptilessuch as Hydrorga leptonyx (Nelson et al, 2013), Peromyscus maniculatus (Schmidt et al, 2019), Macaca mulatta (Chen et al, 2019) and Shinisaurus crocodilurus (Jiang et al, 2017), Crocodylus siamensis (Lin et al, 2019), and Brachylophus vitiensis (Eliades et al, 2021)-have confirmed that captivity may change the composition and abundance of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geckos were captured by hand between 1600 and 0200 h and for all locality records we used the WGS-84 datum. We collected cloacal swabs to inventory host-associated gut microbial communities, which have been shown to be effective proxies for endogenous microbiome sampling in reptiles (Colston et al 2015 , Eliades et al 2021 ). To collect cloacal microbiome samples, we inserted sterile rayon-tipped swabs approximately 3 cm into the cloacal opening of each animal and rotated them 10 times (Smith et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%